Aggregation-induced chirality, circularly polarized luminescence, and helical self-assembly of a leucine-containing AIE luminogen. Issue 10 (29th January 2015) - Li, Hongkun; Cheng, Juan; Deng, Haiqin; Zhao, Engui; Shen, Bo; Lam, Jacky W. Y.; Wong, Kam Sing; Wu, Hongkai; Li, Bing Shi; Tang, Ben Zhong
Abstract : TPE-Leu, an AIE luminogen, shows aggregation-induced chirality, and can self-assemble into helical micro/nanofibers, displaying good circularly polarized luminescence performance. Abstract : Self-assembling of luminescent molecules into one-dimensional nanostructures is of particular interest in fabricating nanoscale electronic and photonic devices. Herein, we report the rational design and synthesis of a chiral fluorescent tetraphenylethylene derivative containingl -leucine methyl ester moiety (TPE-Leu ). In solution, TPE-Leu is non-emissive and CD silent, but becomes highly emissive and CD active upon aggregation, exhibiting aggregation-induced emission (AIE) and chirality (AIC). Upon evaporation of its solution, TPE-Leu readily self-assembles into helical fluorescent micro/nanofibers, which show circularly polarized luminescence (CPL) and have the CPL dissymmetry factors in the range of 0.02–0.07. This molecular design combines the AIE effect, chirality, and self-assembling capability together, and is highly efficient in constructing novel functional micro/nanomaterials with well-defined structures and enhanced emission.